1954
DOI: 10.1037/h0054540
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic avoidance learning: the principles of anxiety conservation and partial irreversibility.

Abstract: The purpose of this paper is to describe two particular ideas, which we shall call "anxiety conservation" and "partial irreversibility," within a general theory of anxiety and avoidance learning. In doing so, more familiar postulates appear to us to generate some new and interesting theorems about behavior, some of which seem to correspond to established facts. We shall not concern ourselves at this time with an exhaustive review of empirical data. Rather, we shall direct our attention to a theoretical argumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
211
1
3

Year Published

1961
1961
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(225 citation statements)
references
References 44 publications
(76 reference statements)
10
211
1
3
Order By: Relevance
“…If, however, one blocks the response, the model is exposed to states d/on/off/2 through d/on/off/4, which elicit fear. The same ideas explain why animals (Solomon & Wynne, 1954) and the model exhibit increased fear when they respond with longer-than-usual latencies.…”
Section: Findings Consistent With Two-factor Theorymentioning
confidence: 68%
“…If, however, one blocks the response, the model is exposed to states d/on/off/2 through d/on/off/4, which elicit fear. The same ideas explain why animals (Solomon & Wynne, 1954) and the model exhibit increased fear when they respond with longer-than-usual latencies.…”
Section: Findings Consistent With Two-factor Theorymentioning
confidence: 68%
“…1 and 2, predictions derived from the theories of Mowrer (1951) and Solomon & Wynne (1954) seem to be supported. Experime~tal animals, which had been blocked for varying periods of time in the presence of the fear provoking Situation, gave fewer responses and responded with greater latencies than control animals.…”
Section: Resultsmentioning
confidence: 71%
“…Mowrer (1951) has suggested that there are two distinct learning processes-the classical conditioning of fear and the instrumental conditioning of the avoidance response-occurring in the acquisition of an avoidance habit. Solomon & Wynne (1954), following Mowrer's paradigm, proposed the anxiety conservation hypothesis to explain the relatively greater perSistence of habits acquired under aversive stimulation. The present study was based upon two predictions derived from these theories: (1) If there are two distinctlearningprocesses in avoidance learning, then one should be able to extinguish one process (fear) separately, and by doing so facilitate extinction of the other (hurdle-jumping); (2) If the anxiety conservation hypothesiS is correct, then blocking the animal in the presence of fear-provoking situations should allow for the full fear reaction to occur and consequently result in its extinction.…”
mentioning
confidence: 99%
“…But as they achieve a solution, e.g., learn the predictive relationships between a CS and US, their excitability generally declines. Indeed, in some cases, subjects will sleep between trials as when dogs had solved a shuttlebox avoidance problem and leisurely awoke to the CS presentation and performed the required response in plenty of time to avoid shock [11].…”
Section: Introductionmentioning
confidence: 99%